Cloud Computing in Financial Technology: Applications and Challenges - Shenghua Dai (Innovation in Science and Technology, 2024)
In the rapid development of Financial Technology (FinTech), cloud computing technology has played a crucial role. This paper aims to explore the applications of cloud computing in the field of FinTech, including payment systems, banking operations, investment management, insurtech, and regulatory technology. At the same time, this paper will also analyze the challenges brought by these applications, such as data security and privacy protection, regulatory compliance, technological dependence and risk management, and technological integration and migration issues. Through an in-depth analysis of these challenges, this paper aims to propose effective solutions and best practices to promote the healthy development of cloud computing in FinTech. The importance of the research lies in the fact that with the continuous innovation of FinTech, cloud computing has become a key factor in driving the transformation of financial services, and understanding and addressing related challenges is crucial for ensuring the stability and security of the financial system. The structure of this paper will be unfolded according to the technical foundation of cloud computing, application cases, challenge analysis, solutions, and future trends, to provide a comprehensive perspective.